2016
DOI: 10.3171/2016.1.spine151317
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile and probe placement accuracy of intraspinal pressure monitoring for traumatic spinal cord injury: Injured Spinal Cord Pressure Evaluation study

Abstract: OBJECTIVE A novel technique for monitoring intraspinal pressure and spinal cord perfusion pressure in patients with traumatic spinal cord injury was recently described. This is analogous to monitoring intracranial pressure and cerebral perfusion pressure in patients with traumatic brain injury. Because intraspinal pressure monitoring is a new technique, its safety profile and impact on early patient care and long-term outcome after traumatic spinal cord injury are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 27 publications
(32 reference statements)
2
47
0
2
Order By: Relevance
“…To rationalise blood pressure management, we monitored intraspinal pressure (ISP) and spinal cord perfusion pressure (SCPP=MAP−ISP) from the injury site 3. Our technique is safe4 and analogous to monitoring intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in traumatic brain injury (TBI). The data indicate that, after TSCI, ISP rises and SCPP falls 3.…”
Section: Introductionmentioning
confidence: 99%
“…To rationalise blood pressure management, we monitored intraspinal pressure (ISP) and spinal cord perfusion pressure (SCPP=MAP−ISP) from the injury site 3. Our technique is safe4 and analogous to monitoring intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in traumatic brain injury (TBI). The data indicate that, after TSCI, ISP rises and SCPP falls 3.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that simultaneous monitoring of SCPP and microdialysis could be used to enhance drug entry at the injury site. Based on our current findings and earlier studies [4][5][6][7][8][9]20,21 , a large-scale study of outcome from TSCI in patients who have monitoring vs. those who do not is warranted.…”
Section: Annals Of Neurologymentioning
confidence: 62%
“…6 Monitoring ISP and SCPP for up to a week is safe based on a review of 42 patients. 7 Data obtained from human 8,9 and mouse 10 studies show that, post-TSCI, the injured spinal cord swells and becomes compressed against the dura. Three intradural compartments form (above, at, and below the injury site), each with a different ISP.…”
mentioning
confidence: 99%
“…When the spinal cord is swollen and compressed against the dura, the subdural pressure (i.e., ISP) and intraparenchymal pressure at the injury site are the same. In this case, ISP is higher than cerebrospinal fluid (CSF) pressure above or below the injury site—details are given elsewhere [5, 6, 1315]. …”
Section: Methodsmentioning
confidence: 99%
“…To guide the management of patients with acute, severe TSCI in the intensive care unit, we introduced intraspinal pressure (ISP) monitoring from the injury site [4, 5]. The technique is safe [6] and allows us to compute the spinal cord perfusion pressure (SCPP) as mean arterial pressure (MAP) minus ISP and the spinal pressure reactivity index (sPRx) as the running correlation coefficient between ISP and MAP. sPRx measures the pressure reactivity of the vascular bed, i.e., autoregulation.…”
Section: Introductionmentioning
confidence: 99%